PERBANDINGAN HAK DAN KEWAJIBAN PEMEGANG IZIN TINGGAL TETAP DI INDONESIA DAN GREEN CARD DI AMERIKA SERIKAT: A Comparative Study of the Rights and Obligations of Foreign Nationals Holding Permanent Stay Permits and Green Cards - Muhamad Daffa Prayoga; Tri Sulistyowati (Faculty of Law, Universitas Trisakti, 2025)
This study compares the rights and obligations of foreign nationals (FNs) holding a Permanent Stay Permit (KITAP) in Indonesia and those holding a Green Card in the United States, with the problem on the legal implications for their family members. The research is based on increasing global mobility, which demands a clear and fair immigration system. Using a normative juridical method and comparative approach, the study analyzes immigration laws and relevant legal literature in both countries. The result and conclusion show that KITAP grants limited residency and work rights with strict administrative obligations, such as periodic reporting and tax compliance. In contrast, the U.S. Green Card offers permanent residency, employment rights, and a path to naturalization without routine reporting. Regarding families, KITAP holders may apply for residence visas and access public services under administrative requirements as regulated in Ministry Regulation No. 22 of 2023. These differences reflect each country’s immigration policy orientation in balancing sovereignty with legal protection for FNs.